Understanding and Implementation of Corporate Social Responsibility in the Peruvian Context - Torres Risco, Liliana Cecilia (2011)
In the last decades Corporate Social Responsibility - CSR has become a form of business management which seeks to incorporate the different expectations and needs not only of companies but also of society as a whole, in such a way there may be a mutual and long term benefit. In line with this, CSR has taken greater importance in developing countries as an alternative to alleviate poverty and promote sustainable development, however the way in which it is interpreted and implemented can vary widely and is significantly influenced by the context in which it takes place. This dissertation investigates how companies operating in Peru conceive social responsibility management and how this understanding is adjusted by the surrounding context. In that sense, through the analysis of sustainability reports and applying the Business and Context framework, this research demonstrates the progress, differences and similarities of CSR in Peru with reference to a decade ago and what are the trends manifested today in the country. The results of the study shows that although in terms of interpretation and domain of CSR discourse as a business management approach companies in Peru reveal a progress, activities, trends and drivers have not changed significantly the last years. Nevertheless, among the social actions analyzed it can be found examples of programmes that achieved a win-win relation without creating dependency with the initial support, it means, a sustainable initiative. These experiences are key in the sense that it can be identified certain factors that have been successfully implemented in the Peruvian context and can be used as a reference for future social responsible practice.